Pendidikan Prakarya dan Kewirausahaan Pada Era Revolusi Industri 4.0 - Asri Solihat; Syamsu Yusuf (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
Abstract– The era of education released by the industrial revolution 4.0 is called Education 4.0, which is characterized by digital technology in the learning process known as the cyber system and is able to create a continuous learning process without space and time limits. The challenges of education in the 4.0 industrial revolution era specifically in Indonesia also spoke of competencies that were able to compete with developments. The method used in this study is an explanatory survey with a simple random sampling technique of 130 respondents. The data analysis technique used is simple regression analysis with SPSS 23.0 for Windows. The results show that the exhibition of Education and Entrepreneurship in the Industrial Revolution Era 4.0 fits the good category.